Lonely, Misunderstood, Isolated…: An Approach to Male Narrators in Federico Jeanmaire’s Narrative - Caño Rivera, Claudia (2023)
The main goal in this paper is to analyze the narrator of the novels Papá (2003), La patria (2006), Wërra (2020), Darwin o el origen de la vejez (2022) e Historia íntima del amor masculino (2022), by the Argentinian writer Federico Jeanmaire, from a gender perspective focused on the study of new masculinities. These autobiographic novels are characterized by being narrated in first person by a narrator that functionss a transposition of the author himself, who recalls his life experiences. Particularly, the paper focuses on investigating the relation between the narrator and hegemonic masculinities and its institutions, as well as on attitudes he unfolds in his own emotions or in the romantic love.